Let There Be Enlightenment : The Religious and Mystical Sources of Rationality - Matytsin, Anton M., 1985- (Book collections on Project MUSE., 2018)
According to most scholars, the Enlightenment was a rational awakening, a radical break from a past dominated by religion and superstition. But in Let There Be Enlightenment, Anton M. Matytsin, Dan Edelstein, and the contributors they have assembled deftly undermine this simplistic narrative. Emphasizing the ways in which religious beliefs and motivations shaped philosophical perspectives, essays in this book highlight figures and topics often overlooked in standard genealogies of the Enlightenment. The volume underscores the prominent role that religious discourses continued to play in major aspects of seventeenth- and eighteenth-century thought.